Pengaruh Model Pembelajaran Berbasis Proyek Terhadap Kemampuan Berpikir Kreatif Mata Pelajaran Pendidikan Pancasila Pada Siswa Kelas V Sdn 83 Padang Setang - Nur Atika Agus (CV. SINAR HOWUHOWU, 2026)
This research was motivated by the low creative thinking skills of students in the Pancasila Education subject in grade V at SDN 83 Padang Setang, Maros Regency. This situation is shown by the students' lack of ability to express ideas and solve problems. This study aims to find out: (1) an overview of the implementation of a project-based learning model; (2) an overview of students' creative thinking skills; and (3) the effect of the project-based learning model on students' creative thinking skills. This study uses a quantitative approach with a quasi-experimental type and a Nonequivalent Control Group Design. The population of this study was all grade V students at SDN 83 Padang Setang, totaling 36 students: 18 students in class VA and 18 students in class VB. These classes also served as the research sample, with class VA as the experimental class and class VB as the control class. Data was collected through observation and tests, then analyzed using descriptive and inferential statistics. The research results show that the implementation of the project-based learning model was carried out well, students' creative thinking skills in the experimental class were better than in the control class, and there was a significant influence of the project-based learning model on the creative thinking skills of fifth-grade students at SDN 83 Padang Setang, Maros Regency.